2017
DOI: 10.6065/apem.2017.22.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Bone modeling, remodeling, and skeletal health in children and adolescents: mineral accrual, assessment and treatment

Abstract: The modeling and remodeling process of the bone is fundamental to maintaining its integrity and mechanical properties. Many physical and biochemical factors during childhood and adolescence are crucially important for the development of healthy bones. Systemic conditions, such as hormonal status, nutrition, physical inactivity, or many pharmacological treatments, as well as a local variation in the load, can influence bone turnover and, consequently, the attainment of a proper peak bone mass. However, many dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 25 publications
0
31
0
1
Order By: Relevance
“…In humans, longitudinal growth occurs until the epiphyseal plate becomes ossified in the late teens and early twenties [69]. However, rat skeleton is considered fully mature only after the age of 10 months.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, longitudinal growth occurs until the epiphyseal plate becomes ossified in the late teens and early twenties [69]. However, rat skeleton is considered fully mature only after the age of 10 months.…”
Section: Discussionmentioning
confidence: 99%
“…In females, correlations were highest in the 18‐year age group and next highest in the 31‐year age group. One factor that may have influenced these results is that males tend to reach their peak height and their overall physical maturity later than females (Maggioli & Stagi, ). This can also be seen in Table when comparing males' and females' heights and weights at different ages.…”
Section: Discussionmentioning
confidence: 99%
“…Peak bone mass (PBM) is well known as a key determinant of the lifetime risk of osteoporosis. (5) It has been reported that the lifetime fracture risk is estimated to decrease by 40% for each 0.5 SD increase in PBM. (6) Therefore, optimizing PBM is considered one of the fundamental ways to prevent osteoporosis.…”
Section: Introductionmentioning
confidence: 99%